Antidotes for poisoning by alcohols that form toxic metabolites. (4th January 2016) - McMartin, Kenneth; Jacobsen, Dag; Hovda, Knut Erik
Abstract : The alcohols, methanol, ethylene glycol and diethylene glycol, have many features in common, the most important of which is the fact that the compounds themselves are relatively non‐toxic but are metabolized, initially by alcohol dehydrogenase, to various toxic intermediates. These compounds are readily available worldwide in commercial products as well as in homemade alcoholic beverages, both of which lead to most of the poisoning cases, from either unintentional or intentional ingestion. Although relatively infrequent in overall occurrence, poisonings by metabolically‐toxic alcohols do unfortunately occur in outbreaks and can result in severe morbidity and mortality. These poisonings have traditionally been treated with ethanol since it competes for the active site of alcohol dehydrogenase and decreases the formation of toxic metabolites. Although ethanol can be effective in these poisonings, there are substantial practical problems with its use and so fomepizole, a potent competitive inhibitor of alcohol dehydrogenase, was developed for a hopefully better treatment for metabolically‐toxic alcohol poisonings. Fomepizole has few side effects and is easy to use in practice and it may obviate the need for haemodialysis in some, but not all, patients. Hence, fomepizole has largely replaced ethanol as the toxic alcohol antidote in many countries. Nevertheless, ethanol remains an important alternative because access to fomepizole can be limited, the cost may appear excessive, or the physician may prefer ethanol due to experience.